Science 1998
DOI: 10.1126/science.282.5395.1846
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness and Complexity

Abstract: Conventional approaches to understanding consciousness are generally concerned with the contribution of specific brain areas or groups of neurons. By contrast, it is considered here what kinds of neural processes can account for key properties of conscious experience. Applying measures of neural integration and complexity, together with an analysis of extensive neurological data, leads to a testable proposal-the dynamic core hypothesis-about the properties of the neural substrate of consciousness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
925
3
11

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,326 publications
(1,000 citation statements)
references
References 85 publications
36
925
3
11
Order By: Relevance
“…They search for specific 'awareness neurons', possibly characterized by a tendency to fire bursts synchronously, and possibly distributed in the cortex (the lower layers), thalamus, and the limbic system (Koch and Crick, 1994). Equally roughly speaking, we can classify the attempts by Tononi and Edelman (1998) as process specific. They look for a specific form of activity in cortical neurons that form a coherent but variable dynamic core as the correlate to consciousness.…”
Section: Macroscopic Effectsfmodification Of Thalamocortical Loop Actmentioning
confidence: 99%
“…They search for specific 'awareness neurons', possibly characterized by a tendency to fire bursts synchronously, and possibly distributed in the cortex (the lower layers), thalamus, and the limbic system (Koch and Crick, 1994). Equally roughly speaking, we can classify the attempts by Tononi and Edelman (1998) as process specific. They look for a specific form of activity in cortical neurons that form a coherent but variable dynamic core as the correlate to consciousness.…”
Section: Macroscopic Effectsfmodification Of Thalamocortical Loop Actmentioning
confidence: 99%
“…Recently, several writers have suggested that this binding is the mechanism of consciousness itself. For example, Tononi and Edelman (1998) propose that the neural process underlying consciousness is a ''dynamic core'' or cluster of neurons in the thalamocortical system that fire synchronously together over a period of several hundred milliseconds. This ''core'' is roughly equivalent to Baars' global workspace (Baars, 1988).…”
Section: Neural-cognitive Basis Of the Nucleusmentioning
confidence: 99%
“…For example, in the experiment of Rodriguez et al, I interpret the period of desynchronization as corresponding to the movement of the stream of consciousness from one substantive thought to another. This equation can possibly explain a number of the phenomenological characteristics of the substantive thoughts: (1) limited capacity: each region of the brain can independently process an immense amount of information, but only a limited amount of information can take part in the global ensemble; (2) stability: a pattern of synchronous firing among disparate brain regions takes several hundred milliseconds to develop-consistent with the 200-500 ms it takes to individuate distinct events (Potter, 1975;Duncan, Ward, & Shapiro, 1994)-and must be maintained for a minimal amount of time in order to be conscious (Tononi & Edelman, 1998); (3) multimodality: information from any sensory modality can be a dominant part of any particular ensemble; (4) sequential processing: only one such ensemble can exist at any one time in the brain; and (5) memorability: the contents of each ensemble are automatically encoded by the medial temporal memory system for subsequent retrieval.…”
Section: Neural-cognitive Basis Of the Nucleusmentioning
confidence: 99%
“…Numerous theories propose that many of the processes that underlie cognition and awareness are sub-served by oscillatory synchrony between brain areas, where, for example, oscillations have to be sustained to carry information (see e.g., Engel et al (2001); Varela et al (2001); Tononi and Edelman (1998)). Because P episode subtracts background activity, it can be much more sensitive than either wavelets or multitapers when conditions differ only slightly from one another, but have distributions that are near the duration or amplitude thresholds of P episode (cf.…”
Section: Discussionmentioning
confidence: 99%